2011
DOI: 10.1007/s10802-011-9601-8
|View full text |Cite
|
Sign up to set email alerts
|

Can Motivation Normalize Working Memory and Task Persistence in Children with Attention-Deficit/Hyperactivity Disorder? The Effects of Money and Computer-Gaming

Abstract: Visual-spatial Working Memory (WM) is the most impaired executive function in children with AttentionDeficit/Hyperactivity Disorder (ADHD). Some suggest that deficits in executive functioning are caused by motivational deficits. However, there are no studies that investigate the effects of motivation on the visual-spatial WM of children with-and without ADHD. Studies examining this in executive functions other than WM, show inconsistent results. These inconsistencies may be related to differences in the reinfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
120
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 142 publications
(135 citation statements)
references
References 50 publications
11
120
0
4
Order By: Relevance
“…La escasa persistencia de alumnos con TDAH se materializa en el LBS en que, por ejemplo, son menos capaces de implicarse en las tareas, no les importa el éxito o el fracaso, o que a pesar de esforzarse pierden la concentración y su rendimiento se deteriora. Estudios experimentales (Dovis, Van der Oord, Wiers, & Prins, 2012) que han analizado los efectos motivacionales del refuerzo muestran que solo en los niños con TDAH, en comparación a niños sin TDAH se produce un decremento con el tiempo en el desempeño de las tareas. El feedback no es suficiente para que los niños sin TDAH logren un desempeño óptimo sino que necesitan un refuerzo extra.…”
Section: Discussionunclassified
“…La escasa persistencia de alumnos con TDAH se materializa en el LBS en que, por ejemplo, son menos capaces de implicarse en las tareas, no les importa el éxito o el fracaso, o que a pesar de esforzarse pierden la concentración y su rendimiento se deteriora. Estudios experimentales (Dovis, Van der Oord, Wiers, & Prins, 2012) que han analizado los efectos motivacionales del refuerzo muestran que solo en los niños con TDAH, en comparación a niños sin TDAH se produce un decremento con el tiempo en el desempeño de las tareas. El feedback no es suficiente para que los niños sin TDAH logren un desempeño óptimo sino que necesitan un refuerzo extra.…”
Section: Discussionunclassified
“…Moreover, the two most frequent treatments in ADHDmedication and behavioral interventions, do not intrinsically provide patients with concrete strategies or skills for coping with associated functional impairments (Chacko et al, 2014 ;Shalev et al, 2007 ;Sonuga-Barke, Brandeis, Holtmann, & Cortese, 2014 ). After the termination of these treatments, no consistent changes were recorded in the neurocognitive measures (Dovis, Van der Oord, Wiers, & Prins, 2012 ;Jarrett, 2013 ). Cognitive training , on the other hand, does aim at improving basic neurocognitive mechanisms that are related to academic skills, as well as to other skills that are impaired in ADHD.…”
Section: Treatments In Adhdmentioning
confidence: 99%
“…Research indeed shows that children with ADHD, in contrast to their TD peers, show suboptimal performance on visuospatial WM-and visuospatial STM tasks under regular reinforcement conditions (e.g., feedback-only), and require relatively high incentives (e.g., feedback ? 10 euros) to perform to their full abilities [13,33,34]. Holmes et al and Lambek et al did not control for these motivational deficits in children with ADHD (both studies used only regular reinforcement conditions), which may have resulted in an overestimation of the prevalence and diagnostic validity of WM and STM impairments in their ADHD samples.…”
mentioning
confidence: 99%
“…Finally, although an abnormal sensitivity to reinforcement (as defined by Haenlein and Caul [28]) might be characteristic for children with ADHD on a group-level (for reviews [39,40]; see also [13,33,34]), the prevalence and diagnostic validity of this motivational deficit within the ADHD population is largely unknown. Only one recent study (de Zeeuw et al [23]) investigated its prevalence in children with ADHD, and found that \8 % of these children could be classified as having an abnormal sensitivity to reinforcement.…”
mentioning
confidence: 99%
See 1 more Smart Citation